Capital Mobility with Convergence in Open Economies - Anton Abdulbasah Kamil (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2006)
The major objective of the paper is to provide a theoretical description of convergence in neoclassicalmodels with various initial ratios of human to physical capital. To avoid immediate convergence,adjustment costs (higher for human capital than for physical capital investment) are introduced. Themodel is calibrated consistently with empirically-observed slow long-run convergence. Economies withhigh initial ratios of human to physical capital are, however, predicted to grow quickly in the shortrun. Moreover, substantial current-account deficits may occur due to high marginal products ofphysical capital and resulting high levels of domestic physical capital investment. This analysisseems relevant to Malaysian economies, which exhibit high ratios of human to physical capital,current-account deficits, and relatively high average growth rates.